Model Pembelajaran Blended Learning yang Bermutu pada Mahasiswa di FITK UIN Maulana Malik Ibrahim Malang - Muh. Hambali (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2020)
The industrial revolution is all life activies using teknology, including in educational institutions that have to improvise learning model. Learning is a process of imitating the example of educators in teaching students' knowledge, attitudes and skills.Lecturers are educators who have the authority to change the way of thinking and how to act towards the development of superior character, so lecturers need competency in the learning model.The learning model requires direct interaction so that the process of seeding values, culture and language manners occurs correctly.This model can be called an offline-based learning process. Offline learning has limited access to reference sources from websites and learning requires face-to-face learning. The referral source facilities available in the campus library are limited, while the online-based referral resource facilities are provided by UIN Maulana Malik Ibrahim Malang. This learning model provides global and fast access while learning and searching for various reference sources. The learning model is blended learning. Blended learning is mixed learning that combines conventional, face-to-face learning models with remote learning using internet networks. Lecturers use an offline process in the form of face to face at the beginning of the lecture to explain the learning scenario. After that, learning uses the e-learning website facility that is owned by UIN Maulana Malik Ibrahim Malang. This research approach uses qualitative, the type of research is a case study. This research will work to find facts on how the implementation of learning activities through blended learning at UIN Maulana Malik Ibrahim Malang. The findings show that the blended learning model is implemented by developing a combination of conventional approaches, namely face-to-face learning using website-based learning, e-learning at UIN Maulana Malik Ibrahim Malang, which then succeeded in improving the quality of student learning.